Peran Media Sosial Dalam Bidang Kardiologi: Suatu Tinjauan Pustaka - Laksono, Sidhi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Advances in trends and digital technology have greatly influenced the health sector with fast access to information. The fields of cardiology and vascular medicine have seen technological advances as great opportunities and experiences in digital platforms uses and social media, respectively. This article aims to look at the role of social media in the field of cardiology. The research method used is the literature review, which searches for appropriate literature about social media in the field of cardiology. In this unprecedented time of the COVID-19 pandemic, social media and other digital platforms are essential tools for communication, education, and information delivery. Social media is used for educational purposes in the form of lectures or case discussions on cardiology topics. In addition, social media is used to build communities and education networks as well as to publish research results, health promotion, and best practices in the field of cardiology. So that the role of social media in the field of cardiology is quite a lot and it is recommended that cardiologists should be wise in using social media.